Use of Task-Based Language Teaching in Contemporary English Teaching Materials for Early Language Teaching in Finnish Schools - Marttila, Vili (My University, 2025)
This thesis studies the use of Task-Based Language Teaching in contemporary English teaching materials for early language teaching in Finnish schools. Early language teaching is a recent phenomenon in the Finnish language education system, which is why little research exists on the English learning materials that have been published after the introduction of The Curriculum Basis for Grades 1-2 A1 Language of 2019 by the Finnish National Agency of Education. Moreover, little analyses exist on the contemporary English teaching materials from the perspective of Task-Based Language Teaching in the Finnish language education. The purpose of this thesis is to determine whether the use Task-Based Language Teaching in English teaching materials meets the criteria set in the current curriculum for language teaching and provide data that could be used in the future development of English Teaching Materials. I have selected two different English teaching materials for early language teaching. The materials will be analysed according to Littlejohn’s Task Analysis Model (2011), which describes tasks appearing in learning materials. Based on the findings of the analysis, Task-Based Language Teaching seems to meet the criteria of the current curriculum for language teaching, and it could be used in future development of English teaching materials. However, it is crucial to focus on developing teacher’s materials, due to the teacher’s significant role in language teaching. Future research could be conducted on a larger scale to cover more materials and tasks and possibly compare them to older materials.
Keywords: Task-Based Language Teaching, Early Language Teaching, Finnish education system, study material analysis, task analysis